KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN KARIMUN - Pamela Satria Graniko; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study is based on a problem that is taken from a phenomenon that occurs in Karimun District Education Office. The Phenomenon that occur in the office of the District Education Office Karimun, are the unoptimal employee's performance. This case can be viewed from some employees who have not run the main duties and functions well. The ability of an employee should be able to provide good service to the community, but this does not happen in Karimun District Education Office. Employees still considered lacking in terms of providing good service.The objective of the research is to investigate the performance of Karimun Bureau staff and the factors that influence the employee of Karimun District Education Office in the working.The research theories of this study are Mangkunegara theory and factor theory that influence perrformance of the employee by Ruky. The research method used is a qualitative research method.Informants in this study is the Head of Education, Secretary of the Department of Education, District Education Office Employees in Karimun, as well as representatives of the community. The results of the interview will be processed using the techniques of data tringulasi.The results of this study indicate that the performance of Karimun Bureau staff have been implemented, but there are still some aspects that have not been appropriate as expected. The result of employee performance have not been up in quality.Keywords: Performance, Employee Performance, Organizations, SDM.